ANALISIS SEBARAN KEBISINGAN AKIBAT AKTIVITAS LANDING DAN TAKE-OFF DI SEKITAR BANDARA INTERNASIONAL SULTAN ISKANDAR MUDA KABUPATEN ACEH BESAR - M. Iswandi (Lingkar : Journal of Environmental Engineering, 2020)
Flight activities at the airport such as takeoffs and landings can cause noise. It can disturb the people who live around the airport. The people who are affected by the aircraft noise over a long period of time will experience health problems. This study aims to determine whether the settlement area around the Sultan Iskandar Muda International Airport is included in the noise area that has been defined. The noise distribution was analyzed using the software Integrated Noise Model. In this study, the noise simulation uses flight data which has been classified for one week based on the flight path used. The result of this study showed that there was one school building in the noise area level I and the settlement in the noise area level II. Further research is needed for seeing the aircraft noise at its peak conditions when the airport is in normal situation, and the aircraft noise mitigation could be done to reduce the impact of aircraft noise.